1974
DOI: 10.3171/jns.1974.41.2.0208
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy after nonmissile depressed skull fracture

Abstract: ✓ Of 1000 patients with nonmissile depressed skull fractures, 10% had early epilepsy (first week) and 15% developed late epilepsy. The risk of late epilepsy varied widely but could be predicted from clinical data 1 week after injury. In more than one-third of the patients with depressed fractures the risk of late epilepsy is less than 4%, but in some patients it is over 60%. The risk is increased if posttraumatic amnesia exceeds 24 hours, if the dura is torn, if there are focal signs, or if there has been earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 10 publications
0
29
1
1
Order By: Relevance
“…involved (21). In civilians, Jennet (22) first stated the close relation between skull fractures complicated by a torn dura and LPTSs.…”
Section: Discussionmentioning
confidence: 99%
“…involved (21). In civilians, Jennet (22) first stated the close relation between skull fractures complicated by a torn dura and LPTSs.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of posttraumatic epilepsy has not been shown to decrease after elevation of a fracture. 1,6 Posttraumatic headaches, learning disabilities, and behavioral problems are unlikely to be caused or improved by surgical intervention. Ten patients did die during their hospital admission as a result of the severe brain trauma; however, no deaths occurred after the initial hospitalization in any group.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the classic recommendation for a simple depressed fracture was to surgically elevate it on the basis of concerns regarding the cosmetic effect, possible underlying pathological features, and epileptogenicity [7]. Since the 1960s, several studies have shown that for children without evidence of neurological or radiographic intracranial lesions, there were no differences between surgically treated and nonsurgically treated patients in terms of future neurological sequels or in the occurrence of seizures [5,8]. …”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is required in cases where the fragments are depressed to the depth of at least one thickness of the skull, and in those with intracranial hematoma, cerebrospinal fluid leak, cosmetically deforming defects, gross wound contamination, and established wound infection [8,9]. …”
Section: Discussionmentioning
confidence: 99%